The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1088/1367-2630/10/7/073021
|View full text |Cite
|
Sign up to set email alerts
|

Orbital ordering and magnetic interactions in BiMnO3

Abstract: Abstract. This work is devoted to the analysis of the orbital ordering patterns and associated interatomic magnetic interactions in the centrosymmetric monoclinic structures of BiMnO 3 , which have been recently determined experimentally. First, we set up an effective lattice fermion model for the manganese 3d bands and derive parameters of this model from first-principles electronic structure calculations. Then, we solve this model in terms of the mean-field Hartree-Fock method and obtain parameters of intera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 56 publications
4
46
1
Order By: Relevance
“…For example, in BiMnO 3 such a mechanism facilitates the formation of the "##" AFM structure, which breaks the inversion symmetry. 16) Nevertheless, in RMnO 3 the situation appears to be different. For all considered compounds, the NN interactions calculated in the E-phase satisfy the following condition: J k 1 ð""Þ < J k 1 ð"#Þ, where the notations "" and "# are referred to the FM and AFM bonds, respectively (Fig.…”
Section: Solution and Analysis Of The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in BiMnO 3 such a mechanism facilitates the formation of the "##" AFM structure, which breaks the inversion symmetry. 16) Nevertheless, in RMnO 3 the situation appears to be different. For all considered compounds, the NN interactions calculated in the E-phase satisfy the following condition: J k 1 ð""Þ < J k 1 ð"#Þ, where the notations "" and "# are referred to the FM and AFM bonds, respectively (Fig.…”
Section: Solution and Analysis Of The Modelmentioning
confidence: 99%
“…16,27,31) After the solution for each magnetic state, the total energy changes corresponding to infinitesimal rotations of the spin magnetic moments near this state were mapped onto the Heisenberg model: 34,35) E Heis ¼ À 1 2…”
Section: Solution and Analysis Of The Modelmentioning
confidence: 99%
“…Therefore the origin of ferroelectricity in these two compounds seems to be different. In BiMnO 3 the emergence of electric moment is connected with inversion symmetry breaking by the AFM order induced by particular orbital order below T = 474 K [42,43]. Another scenario for the onset of electric moment is possible in BiFeO 3 : an extensive investigation of ferroelectricity in BiFeO 3 in the framework of density functional theory was reported in reference [44].…”
Section: Calculated Magnetic Properties Of Bixo 3 (X = Mn Cr Fe)mentioning
confidence: 99%
“…However, the results of recent experiments [7,8] have shown that this ferromagnetic crystal belongs to the C2/c symmetry group, which excludes the exist ence of spontaneous polarization [5][6][7][8][9]. External fac tors (temperature, pressure) can alter the magnetic structure of BiMnO 3 crystals so as to stabilize antifer romagnetism [8,9].…”
Section: Introductionmentioning
confidence: 97%
“…Bismuth manganite BiMnO 3 has been treated in many investigations as a multiferroelectric compound [1][2][3][4][5][6]. However, the results of recent experiments [7,8] have shown that this ferromagnetic crystal belongs to the C2/c symmetry group, which excludes the exist ence of spontaneous polarization [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%